BPDE induced lymphocytic chromosome 3p deletions may predict renal cell carcinoma risk - Zhu, Yimin; Horikawa, Yohei; Yang, Hushan; Wood, Christopher G; Habuchi, Tomonori; Wu, Xifeng (The Journal of urology, 2008)
Cigarette smoking is a risk factor for renal cell carcinoma. BPDE (benzo[alpha]pyrene diol epoxide) (Midwest Research Institute, Kansas City, Missouri), which is a major constituent of cigarette smoke, induces 3p aberrations that are associated with susceptibility to other smoking associated cancers. Because chromosome 3p deletions are known to be the most frequent genetic alterations in renal cell carcinoma, we tested whether 3p sensitivity to BPDE predicts susceptibility to renal cell carcinoma. Cultured peripheral blood lymphocytic cells from 170 cases and 135 controls were treated with 2 microM BPDE for 24 hours and assessed for 3p deletions by fluorescence in situ hybridization using probes directed to 3p25.2, 3p21.3, 3p14.2 and 3p12.2. A probe for 3q13 served as a control. One thousand lymphocyte interphases were scored per sample. At each locus BPDE induced 3p deletions were significantly more common in cases than in controls. No significant differences between cases and controls were observed for deletions in 3q13. Using the median value in controls as the cutoff point for BPDE sensitivity we found that the OR in subjects with high BPDE sensitivity at 3p25.2, 3p21.3, 3p14.2 and 3p12.2 was 2.02 (95% CI 1.18-3.46), 2.28 (95% CI 1.33-3.92), 1.84 (95% CI 1.07-3.16) and 1.97 (95% CI 1.15-3.37), respectively. There were dose dependent relationships between the number of deletions at each locus and the risk of renal cell carcinoma. This study demonstrates that chromosome 3p may be a specific molecular target of cigarette carcinogens and BPDE sensitivity in chromosome 3p may reflect the genetic susceptibility of an individual to renal cell carcinoma.